The implication of protein malnutrition on cardiovascular control systems in rats - Silva, Fernanda C.; de Menezes, Rodrigo C.; Chianca-Jr., Deoclecio A. (Frontiers in Physiology, 2015)
The malnutrition in early life is associated with metabolic changes and cardiovascular impairment in adulthood. Deficient protein intake-mediated hypertension has been observed in clinical and experimental studies. In rats, protein malnutrition also increases the blood pressure and enhances heart rate and sympathetic activity. In this review, we discuss the effects of post-weaning protein malnutrition on the resting mean arterial pressure and heart rate and their variabilities, cardiovascular reflexes sensitivity, cardiac autonomic balance, sympathetic and renin-angiotensin activities and neural plasticity during adult life. These insights reveal an interesting prospect on the autonomic modulation underlying the cardiovascular imbalance and provide relevant information on preventing cardiovascular diseases.